Contribution of The Mysore Province to Literary Translation works in Kannada and English Language - Prasad N., (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2024)
The Mysore Province which was a seat of excellence greatly benefited by the establishment of the Oriental Library, at Mysore in 1891. The Literary translations from other languages to Kannada and vice versa, gained momentum from then and helped the Kannada literary arena, to flourish and bloom into a full-fledged expressive and inclusive modern language. The translations gave a host of novel and fresh literary forms and ideas, which joined forces with the grand repository of existing classic literature. Many literary personalities starting from B M Sri to A K Ramanujan, contributed to the enrichment of Kannada language through their deft translation works. The paper speaks about the contribution of Mysore province for such translatory works, lists out them and their impact on Kannada literature.
Keywords: Oriental; Occidental; Wodeyar; Translation; Verse; Samsthan